Blue Bell's Facebook Posts and Responses During the 2015 Listeria Crisis: A Case Study - Kelsi Opat; Haley Magness; Erica Irlbeck (Journal of Applied Communications, 2018)
Blue Bell Creameries faced an unprecedented situation when it pulled all of its products during a Listeria outbreak in 2015. Despite a very public crisis that resulted in three deaths, Blue Bell survived the disaster and maintained a large and loyal customer base. A content analysis of the Blue Bell Ice Cream Facebook page was conducted to evaluate Blue Bell’s public communications, and its followers’ public reactions to the Facebook communication during the crisis. Results indicated that Blue Bell primarily posted messages that included recall and restocking information, thankfulness to stakeholders, and details about improvements to food safety during the crisis. These messages created a sense of transparency, which can increase customers’ trust and brand loyalty. Their consumers largely responded with comments containing overwhelming loyalty themes as well as questions and messages of thanks. Recommendations for agri-food companies include operating transparently before, during, and after a crisis. Organizations should follow Blue Bell’s example and avoid publishing messages that include attacks, denial, scapegoating, or excuses during a crisis.
Keywords: social media; risk and crisis communication; customer response